Analysis of 1:2 port SIW power divider for 60GHZ short range radar and WLAN applications - Bharath Kumar, K; Shanmuganantham, T (International Journal of Engineering and Technology, 2018)
In this research article, 1:2 port power divider is designed for short-range frequency modulated continuous wave RADAR applications at 60GHz. Substrate Integrated Waveguide technology with coplanar waveguide transmission path is used for the design of 1:2 port power divider. 1:2 port power dividers are designed by using Rogers RT/Duriod 5880 Substrate material. Dielectric constant and electric loss tangent of substrate material is 2.2 and 0.0009 respectively. In this paper first analyzed power divider with its equivalent circuit model and analyzed the characteristic like reflection coefficient, surface and transmission coefficient. 1:2 power dividers give maximum reflection coefficient of -40.33 dB, voltage standing wave ratio of 1.02 and transmission coefficient as 3.142 dB at 60 GHz. This 1:2 power divider gives 2.485 GHz as bandwidth. Dimensions of the 1:2 power divider are 6*10*0.508mm3. Due to its characters, bandwidth and size this 1:2 power divider is suitable for millimeter wave applications like short distance RADAR and WLAN applications of wireless communication systems Â Â